Fast and efficient video completion using object prior position - Zarif, S. (2013)
Reconstruction and repairing damaged parts after object removal of digital video is an important trend in artwork restoration. Video completion is an active subject in video processing, which deals with the recovery of the original data. Most previous video completion approaches consume more time in extensive search to find the best patch to restore the damaged frames. In addition to that, visual artifacts appear when the damaged area is large. In this paper, we present a fast and efficient video completion method without the extensive search process. The proposed method is based on the object prior positions and the temporal continuity of the video frames. The proposed method is fast and maintains the spatial and temporal consistency. In addition to that, it can handle the object size and posture change, non periodic motion, and non stationary background. Â© 2013 Springer International Publishing.